New Brunswick, N.J., Ordinances art. 5, § 33 (1865) - (:unkn) unknown (My University, 1864)
An Ordinance to Establish and Regulate the Fire Department and for the Prevention and Extinguishment of Fires: No person or persons shall store or keep at any time within half a mile of the line of buildings of this city, more than thirty pounds of gunpowder
Keywords: GUNPOWDER - STORAGE